Stem cells-the future of dentistry: A review - Sunil Vyas; Krishna Vyas; Madathanapalli Satish; Vaishali Shende; Rahul Srivastav (Journal of Indian Academy of Oral Medicine and Radiology, 2011)
Research and development in the last millennium and in the present decade has brought about revolutionary changes in the way we understand and treat diseases. Stem cells are one of the most favorable areas of biology. Stem cell plasticity has resulted in a new field of medicine entitled regenerative medicine and dentistry. Scientists have successfully regenerated tooth root and supporting periodontal ligament to restore tooth function in an animal model. The breakthrough in stem cell research holds significant promise for clinical application in human patients.